S1_10 Dangerous Sports: Rugby - Kelliher, Ruth; Geddes, Alex; Peterson, Phil; Cox, Gavin (Physics Special Topics, 2009)
This article explores the damage done to players on the rugby pitch during collisions and tackles. It is found that a dump tackle done by an average 100kg male rugby player on another player exerts a force akin to what a driver would feel in aÂ 30mph car crash into a solid wall. For two players running head-on the force felt is akin to a 40mph crash.